Muslim Pakistan Amerika pada Film Pendek American Eid: Simbolisme Religius dan Harmoni Budaya - Rifka Pratama (Endogami: Jurnal Ilmiah Kajian Antropologi, 2023)
Films often present cultural expressions, religiosity, as well as social criticisms of realities. In fact, films have played a relatively effective role in doing all of the mentioned aspects even in cross socio-cultural situations. Through films, people in Indonesia can observe the reflection of the lives of Muslims in America and vice versa. American Eid depicts the life of a Pakistani American Muslim immigrant family and challenges they face as a minority celebrating their first Eid al-Fitr in America. This article attempts to examine some of the symbolisms that emphasize the religious identity of the main characters of the film and the cultural harmony that exists between Pakistani Muslim traditions and American society. To collect data, I made intensive observations by watching the movie, reading the relevant sources to get the theories, and conducting the analysis through a qualitative method. The results of the study show that there are several religious symbolisms depicted through material and non-material elements as well as the harmony of Pakistani Muslim culture and American society in the context of school life.